Pengaruh Materialisme, Literasi, Sikap, dan Perilaku Keuangan Terhadap Keputusan Menabung Generasi Z di Jakarta - Octavie, Cathy Angelia; Susilawaty, Lilis (Business Management Journal, 2026)
This study examines the factors influencing saving decisions among Generation Z in Jakarta, with a focus on the effects of financial literacy, materialism, as well as financial attitudes and behaviors. The study is motivated by the relatively low saving culture among urban youth despite increasing access to financial technology. Using a quantitative approach, data were collected through questionnaires administered to Generation Z respondents in Jakarta and analyzed using multiple linear regression methods.The results indicate that financial literacy, attitudes, and financial behavior significantly influence saving behavior. In contrast, materialistic orientation does not have a significant effect on the saving behavior of Generation Z. It is recommended to strengthen financial education to promote better financial management practices and to help control unplanned expenditures among Generation Z.